2012
DOI: 10.7708/ijtte.2012.2(4).05
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Private Motorized Trips Indicators in Reducing Car Usage

Abstract: Abstract:Neighborhoods with similar design may have di erent travel behavior due to the impacts of socio-economic indicators. ere are also some e ective indicators such as residents' income, age, and self-selection factors related to this case that cannot be evaluated easily, which question the reliability of previous e orts to describe the e ects of private motorized trips indicators on car usage universally. On the other hand, private motorized trips indicators are e ective factors that in uence travel behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Financial constraints surrounding t he m a i nten a nce a nd operat ion of a mbient mon itor i ng stat ions; conducting oversight studies as well as implementing a package of integrated transport planning and spatial turn measures is hamstrung by lack limited resources (Of f ice of Science and Technology, 2006). Financial resources are essential to ensure the successful implementation and enforcement of sustainable Gauteng public transport agenda (Moeinaddini et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Financial constraints surrounding t he m a i nten a nce a nd operat ion of a mbient mon itor i ng stat ions; conducting oversight studies as well as implementing a package of integrated transport planning and spatial turn measures is hamstrung by lack limited resources (Of f ice of Science and Technology, 2006). Financial resources are essential to ensure the successful implementation and enforcement of sustainable Gauteng public transport agenda (Moeinaddini et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Source: (Research Findings, 2016) Low-density sprawl and fragmentation were (are) characteristic of the Gauteng region contributing to access constraints and temporal spatial structural disjuncture that comprises challenges that Gauteng province is grappling to resolve (SACN, 2014). Studies and research have shown that establishing transport authorities in regions like Gauteng province such as experiences from Netherlands and France can contribute to enhancing commuting (Moeinaddini et al, 2012;UITP, 2015).…”
Section: Snmentioning
confidence: 99%
See 1 more Smart Citation
“…PRT has also been chosen as one of the modes of transportation in the world's first zero emission sustainable city project of Masdar City in United Arab Emirates (De Graff, 2011). Several researchers have recommended ways to reduce the share of private vehicle trips in cities (Moeinaddini et al, 2012;Kumar et al, 2013). PRT is also one of the potential solutions to this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Since transport sector is one of the main contributors to GHG emissions in urban areas, mitigation measures are inescapable regarding climate-oriented studies (Moeinaddini et al, 2012). Beside this importance of mitigation concerning transportation, it must be emphasized that mitigation and adaptation measures inextricably connected in aiming to create comprehensive and future-oriented urban climate plans.…”
Section: Mitigation In Urban Transport Sectormentioning
confidence: 99%